Recurrence Patterns After IMRT/VMAT in Head and Neck Cancer - Bollen, Heleen; van der Veen, Julie; Laenen, Annouschka; Nuyts, Sandra (Frontiers in Oncology, 2021)
Purpose: Intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT), two advanced modes of high-precision radiotherapy (RT), have become standard of care in the treatment of head and neck cancer. The development in RT techniques has markedly increased the complexity of target volume definition and accurate treatment delivery. The aim of this study was to indirectly investigate the quality of current TV delineation and RT delivery by analyzing the patterns of treatment failure for head and neck cancer patients in our high-volume RT center. Methods: Between 2004 and 2014, 385 patients with pharyngeal, laryngeal and oral cavity tumors were curatively treated with primary RT (IMRT/VMAT). We retrospectively investigated loco-regional recurrences (LRR), distant metastases (DM) and overall survival (OS). Results: Median follow-up was 6.4 years (IQR 4.7 – 8.3 years) during which time 122 patients (31.7%) developed LRR (22.1%) and DM (17.7%). Estimated 2- and 5-year loco-regional control was 78.2% (95% CI 73.3;82.3) and 74.2% (95% CI 69.0;78.8). One patient developed a local recurrence outside the high dose volume and 5 patients developed a regional recurrence outside the high dose volume. 4 patients (1.0%) suffered a recurrence in the electively irradiated neck and 2 patients had a recurrence outside the electively irradiate neck. No marginal failures were observed. Estimated 2- and 5-year DM-free survival rates were 83.3% (95% CI 78.9; 86.9) and 80.0% (95% CI 75.2; 84.0). Estimated 2- and 5-year OS rates were 73.6% (95% CI 68.9;77.8) and 52. 6% (95% CI 47.3;57.6). Median OS was 5.5 years (95% CI 4.5;6.7). Conclusion: Target volume definition and treatment delivery were performed accurately, as only few recurrences occurred outside the high-dose regions and no marginal failures were observed. Research on dose intensification and identification of high-risk subvolumes might decrease the risk of locoregional relapses. The results of this study may serve as reference data for comparison with future studies, such as dose escalation or proton therapy trials.